Management of Zakat Funds at Amil Zakat Baitulmal Mu’amalah to Empower People - Edy Saputra; Mohdari Mohdari; Ellis Siti Khotijah; Abdul Rifan Syarif; Dais Farida; Nur Asrofah Sedyo Ningrum (International Journal of Management Science and Application, 2022)
This paper aims to identify the zakat as sepnding part certain from treasure certain have until the Nisabah for the right people accept it. There are 166 million of Muslims in Indonesia (83 % of Indonesia's population is 204.8 million), assumed as muzakki. Muzakki is 18 %, and the potential for zakat in Indonesia is 19.3 trillion per year.  This research was a qualitative approach in the form of a case study. Sources and types of data using data primer. The results showed that management of zakat funds at the Amil Zakat Institute Baitul Maal Muamalat already fulfills standard management which covers management finance in the form of collection, distribution, recipient of funds, field program objectives, form and nature distribution, disbursement of funds, accountability, and management fund balance. From this research, we can get data related to the mechanism for collecting and distributing zakat funds and can be used as research and addition of knowledge.